Identification of IL-17A-derived neural cell type and dynamic changes of IL-17A in serum/CSF of mice with ischemic stroke. (3rd June 2017) - Li, Shujuan; Dai, Qingqing; Yu, Jinling; Liu, Ting; Liu, Shuiqiao; Ma, Longhui; Zhang, Ying; Han, Song; Li, Junfa
Abstract: Background: Interleukin (IL)-17A was reported to be involved in the development of post-ischemic stroke inflammatory response and functional recovery. However, the IL-17A dynamic changes in serum/cerebrospinal fluid (CSF) and its role in neuronal injury following ischemic stroke are unclear. Methods: In vivo ischemic stroke was induced by 1 h of middle cerebral artery occlusion (MCAO) and 6 h-7 d reperfusion (R) in mice, while in vitro stroke was induced by 1 h oxygen-glucose deprivation (OGD)/24 h reoxygenation (R) in cultured cortical neurons. Enzyme-linked immunosorbent assay (ELISA) and double-labeled immunofluorescence of IL-17A with neuron (NeuN), astrocyte (GFAP) and microglia (Iba-1)-specific markers were used to determine the IL-17A levels in serum/CSF and neural cell type. Results: The ELISA results showed that IL-17A significantly increased both in peri-infarct region ( p  < 0.001) and CSF ( p  < 0.05) following 1 h MCAO/R 12 h. The levels of IL-17A in serum increased at R 1 d ( p  < 0.05) and peaked at R 3 d ( p  < 0.001) after 1 h MCAO. Immunofluorescent staining demonstrated that IL-17A co-localized with GFAP in peri-infarct regions. In addition, recombinant rIL-17A could aggravate ischemic injuries at dose-dependent manner in 1 h OGD/R 24 h-treated neurons companying with the increase of IL-17A receptor il - 17RA mRNA ( p  < 0.001) and IL-17R protein levels. Conclusion: We firstly reported astrocytic IL-17A peaks in CSF within 12 h and in serum at 3 d reperfusion after ischemic stroke. IL-17A may exaggerate neuronal injuries through its receptor IL-17R at early stage of ischemic stroke.